A BRIEF OVERVIEW- MOLECULAR BASIS OF ANTIMICROBIAL RESISTANCE - K. N. PAVANKUMAR; H. S. MADHUSUDHAN; N. CHANDRASHEKHARA (International Journal of Pharma and Bio Sciences, 2014)
Antibiotics play a vital role in the treatment of bacterial infections in both humans and animals. As a result antibiotic resistance develops, posing serious health problems in both humans and animals. This has led to concerns about the public health implications of antibiotic use in animal husbandry. To avoid elimination by antibiotic substances, bacteria develop resistance by mutation or by acquisition of genes from other bacteria. Horizontal gene transfer between bacteria is a common event and an important factor in microbial evolution. These antibiotic resistant bacteria get into human food chain posing a potential risk. Transmission of resistant gene between different species occurs. Resistance genes can persist in the environment both in their original bacterial hosts and in transferred organisms. Resistance becomes a problem when a bacterium causing a disease withstands antibiotic therapy. Increased resistance to antibiotics may therefore cause clinical problems and may shorten the useful life span of some antibiotics. The present paper highlights their mode of entry into food chain, various biochemical methods by which bacteria develops resistance, possible health problems and measures to control antibacterial resistance.